2020
DOI: 10.1038/s41550-020-1120-5
|View full text |Cite|
|
Sign up to set email alerts
|

Resonance locking in giant planets indicated by the rapid orbital expansion of Titan

Abstract: Tidal effects in planetary systems are the main driver in the orbital migration of natural satellites. They result from physical processes occurring deep inside celestial bodies, whose effects are rarely observable from surface imaging. For giant planet systems, the tidal migration rate is determined by poorly understood dissipative processes in the planet, and standard theories suggest an orbital expansion rate inversely proportional to the power 11/2 in distance 1 , implying little migration for outer moons … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
196
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(237 citation statements)
references
References 42 publications
19
196
0
Order By: Relevance
“…Since Titan is in the close-in regime, its outward migration produces an increase in α. The migration rate of Titan recently measured by Lainey et al (2020) supports the tidal theory of Fuller et al (2016), through which the time evolution of Titan's semi-major axis can be expressed as…”
Section: Precession Constantsupporting
confidence: 58%
See 2 more Smart Citations
“…Since Titan is in the close-in regime, its outward migration produces an increase in α. The migration rate of Titan recently measured by Lainey et al (2020) supports the tidal theory of Fuller et al (2016), through which the time evolution of Titan's semi-major axis can be expressed as…”
Section: Precession Constantsupporting
confidence: 58%
“…For years, the scenarios that were most successful in reproducing Saturn's current obliquity through this resonance invoked the late planetary migration Boué et al 2009;Vokrouhlický & Nesvorný 2015;Brasser & Lee 2015). However, Saillenfest et al (2021) have recently shown that this picture is incompatible with the fast tidal migration of Titan detected by Lainey et al (2020) in two independent sets of observations -assuming that this migration is not specific to the present epoch but went on over a substantial interval of time. Indeed, satellites affect the spin-axis precession of their host planets (see e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed current fast tidal orbital expansion rate (Lainey et al 2012(Lainey et al , 2017 and observations of the rings by Cassini suggest late formation of the satellites (see, e.g., Ida 2019) such as the formation model from a hypothetical ancient massive rings (Charnoz et al 2011;Crida & Charnoz 2012), which we refer to as the disk. We note, however, that a possible slower tidal orbital expansion rate in the past, before resonance locking between the orbital frequency and the planetary internal oscillation mode, could allow the satellite formation in the circumplanetary disk 4.5 G years ago (Lainey et al 2020).…”
Section: Introductionmentioning
confidence: 82%
“…The only known heat source able to maintain water liquid on tiny Enceladus is from the dissipation of tides raised by Saturn. Where energy is dissipated is uncertain: water flowing through a permeable rocky core (Choblet et al, 2017), ocean movement damped by the overlying ice (Tyler, 2020), and/or recently increased equilibrium forcing of the ice shell if Enceladus' orbit is expanding at a nearly constant rate due to changes in Saturn's interior (Nimmo et al, 2018;Lainey et al, 2020). Each mechanism could alone sustain the current ocean.…”
Section: Sufficient Amount Of Time For Life To Emergementioning
confidence: 99%